The Pseudo-Laplace Filter for Vector-Based Elastic Reverse Time Migration - Du, Qizhen; Zhang, Xiaoyu; Zhang, Shukui; Zhang, Fuyuan; Fu, Li-Yun (Frontiers in Earth Science, 2021)
In vector-based elastic reverse time migration, the scalar images (PP and PS) can be eﬀectively obtained by applying dot product-based scalar imaging conditions to the vector wavefields. However, the PP image suffers from polarity reversal problem while opening angles are greater than 90° and backscattering artifacts while opening angles are near 180°. To cope with these above-mentioned issues, we propose the pseudo-Laplace filter for the dot product-based scalar imaging condition. Based on the analysis of Laplace filter in scalar image of vector-based wavefields, the 2-nd parallel-oriented partial derivatives of Cartesian components cross-correlation results are selected to construct the pseudo-Laplace filter, omitting 2-nd normal-oriented partial derivatives of Cartesian components cross-correlation results. Theoretical analysis with assumption of plane wave has proved that the proposed pseudo-Laplace filter can solve the problems of backscattering artifacts and polarity reversal in PP image through scalar imaging condition. Numerical examples show excellent performance in PP image with pseudo-Laplace filter due to additional polarity correction and backscattering attenuation. Besides, the application of the pseudo-Laplace filter requires little additional computation or storage.